Fact vs. fiction : teaching critical thinking skills in the age of fake news - LaGarde, Jennifer; Hudgins, Darren (International Society for Technology in Education, 2018)
The advent of the 24-hour news cycle, citizen journalism and an increased reliance on social media as a trusted news source have had a profound effect not only on how we get our news, but also on how we evaluate sources of information, share that information and interact with others in online communities. When these issues are coupled with the "fake news" industry that intentionally spreads false stories designed to go viral, educators are left facing a new and challenging landscape. This book will help them address these new realities. Fact vs. Fiction provides educators with tools and resources to help students discern fact from fiction in the information they access not only at school, but on the devices they carry in their pockets and backpacks.